Reimagining life and death: Results and interpretation of geophysical and ethnohistorical investigations of earth mounds, Mapoon, Cape York Peninsula, Queensland, Australia. Issue 2 (12th April 2019) - ST PIERRE, EMMA; CONYERS, LAWRENCE; SUTTON, MARY‐JEAN; MITCHELL, PETER; WALKER, CHESTER; NICHOLLS, DIANNE
ABSTRACT: Ground‐penetrating radar (GPR) and magnetic surveys were conducted on 13 earth mounds within Mapoon Aboriginal Lands, western Cape York Peninsula, Queensland. Detailed analysis of GPR profiles and amplitude maps of the mounds were compared to those from previously recorded, known burials at the Mapoon Mission Cemetery. Based on these models, burials were identified in ten of the 13 mounds. Both European‐style (coffin) and traditional burials were identified, suggesting that they were used for human interment for some time and that there may have been continuity of burial practice in these features after European contact. GPR and magnetics also indicate that a number of mounds had constructed floors or platforms at the base of the mounds, and evidence for burning. Stratigraphic layers identified with GPR show that many of these mounds have complex internal layering, suggesting multiple building episodes. Based on the GPR and magnetics results, in conjunction with ethnohistorical and oral history research, we conclude that the mounds are constructed features that appear to have had a long history of use for multiple purposes, including mortuary. These results demonstrate the cultural continuity of mortuary practices within Mapoon from pre‐contact times to the present. Abstract : Ground‐penetrating radar (GPR) and magnetic surveys were conducted on 13 earth mounds within Mapoon Aboriginal Lands, western Cape York Peninsula, Queensland. Analysis of the geophysical data were compared to models of known burials in the area. Based on this analysis, burials were identified in ten of the 13 mounds; both European‐style (coffin) and traditional burials. The results also indicate that a number of mounds had constructed floors or platforms at their bases, evidence for burning and complex internal layering, suggesting multiple building episodes. Based on these results, in conjunction with ethnohistorical and oral history research, we conclude that the mounds are constructed features that appear to have had a long history of use for multiple purposes, including mortuary, and demonstrate the cultural continuity of mortuary practices within Mapoon from pre‐contact times to the present. RÉSUMÉ: Des relevés géo‐radar ou encore appelés radar de pénétration au sol (GPR) et magnétique ont été effectués sur 13 monticules de terre situés sur les terres autochtones de "Mapoon", dans I'ouest de la péninsule du Cap York, dans le Queensland en Australie. Une analyse détaillée de ceb profils et des cartes d'amplitude des monticules, a été comparée à celles d'enterrements connus et précédemment enregistrés dans le cimetière de la mission de "Mapoon". À partir de ces relevés, des inhumations ont été trouvées dans dix des 13 monticules. Des sépultures traditionnelles, de style européen (en cercueil) ont été identifiées, suggérant qu'elles étaient utilisées pour I'enterrement d'humains et qu'il pourrait y avoir eu une continuité de la pratique de I'inhumation après les premiers contacts avec une civilisation européenne. Ces analyses indiquent également qu'un certain nombre de monticules avaient des sols ou des plates‐formes construits à leurs bases, ainsi que des traces de brûlures. Les couches stratigraphiques identifiées avec géo‐radar montrent que beaucoup de ces monticules présentent une stratification interne complexe, suggérant de multiples épisodes de construction. À partir de ces résultats, ainsi que de la recherche en histoire ethno‐historique et orale, nous concluons que les monticules ont des caractéristiques de construction démontrant une utilisation à des fins multiples, y compris en tant que morgue. Ces résultats démontrent la continuité culturelle des pratiques mortuaires au sein de la mission de "Mapoon" depuis les temps précédant le contact avecu une civilisation européenne et continué de nos iours.